Breath and Beyond: Advances in Nanomedicine for Oral and Intranasal Aerosol Drug Delivery - Simeng Du; Zhiyang Wen; Jinghan Yu; Yingying Meng; Yuling Liu; Xuejun Xia (Pharmaceuticals)
Designing and standardizing drug formulations are crucial for ensuring the safety and efficacy of medications. Nanomedicine utilizes nano drug delivery systems and advanced nanodevices to address numerous critical medical challenges. Currently, oral and intranasal aerosol drug delivery (OIADD) is the primary method for treating respiratory diseases worldwide. With advancements in disease understanding and the development of aerosolized nano drug delivery systems, the application of OIADD has exceeded its traditional boundaries, demonstrating significant potential in the treatment of non-respiratory conditions as well. This study provides a comprehensive overview of the applications of oral and intranasal aerosol formulations in disease treatment. It examines the key challenges limiting the development of nanomedicines in drug delivery systems, formulation processes, and aerosol devices and explores the latest advancements in these areas. This review aims to offer valuable insights to researchers involved in the development of aerosol delivery platforms.